Self-Concept as a Result of Personality Disorder Portrayed in Haruki Murakami’s 'Norwegian Wood' - Permatasari, Indah; Rosyidi, Mohamad Ikhwan (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
This research is carried out to find out how Borderline Personality Disorder influencing an individual self-concept in Haruki Murakami’s Norwegian Wood. There are several research methods used in this study, they are library research and descriptive qualitative research. By using the library research method, the writer found the data and references dealing with the topic analysis. The data then is written in descriptive in order to answer the research questions, the writer also employed psychoanalysis theory by Sigmund Freud to analyze how self-concept is the result of Borderline Personality Disorder. The result indicates that Naoko, the center of the research, is struggling to survive because she has a traumatic past events. The character developed five criteria of a person to have Borderline Personality Disorder, they are problem with relationships, unstable emotions, unstable identity, impulsive and self-damaging behavior, and unstable thinking/cognition which developed by the character. Then, there are defenses, anxiety and core issues that influence the behavior of the character. Self-concept is using by the represented character as the result of borderline personality disorder that revealed in the id, ego, and superego.